Trends in animal production from organic farming [review] - Wojciech Wójcik; Paweł Solarczyk; Monika Łukasiewicz; Kamila Puppel; Beata Kuczyńska (ACTA INNOVATIONS, 2018)
Organic farming is an alternative method for dynamic agricultural system. Products that are obtained from organic farming are referred to as ecological or organic food [1]. These include products of animal origin that come from organic farming [2]. In the case of animal production in organic farming there are particular requirements for breed, animal welfare and feeding. Additionally, the origins of animals is also of crucial importance since, basically, such animals should be purchased from organic farms. However, there can be exceptions to this requirement, for instance, if the number of animals of a particular species or of a specific breed is not sufficient [3]. The main idea behind organic production is obtaining plant or animal products maintaining good soil structure, clean water and adjusting to the natural rhythm of nature. Enhancement of the social status has led to the situation where consumers pay more attention to the quality and origins of the products they choose. Numerous scientific papers from recent years, based on consumer’s opinion, show substantial impact of welfare system on the quality of animal products. Since ‘90s there has been a systematic surge of interest in products from ecological systems and demand for these, which in turn affect the development of this agricultural sector. The aim of the work is to compare the changes in organic production over the last 26 years in Poland with reference to the situation in Europe and whole globe. The research has been done on the basis of statistics since 1990 up till now as well as on scientific studies. Nowadays, there are increasing numbers of farms and redirections of production, as well as changes in the sizes of farms producing organic food.